1992
DOI: 10.3928/0191-3913-19920301-05
|View full text |Cite
|
Sign up to set email alerts
|

Normal Intraocular Pressure in Children

Abstract: The age-related trend values and the normal intraocular pressure (IOP) increase curve from birth through the 16th year of life were studied in 460 subjects with a noncontact tonometer (Keeler Pulsair, Keeler, Ltd, Windsor, Berks, UK). Much lower values than in adults were recorded in subjects up to the age of 3 or 4 years. This finding leads us to believe that in the treatment of infantile glaucoma IOP should be kept within the age physiologic levels, in an attempt to prevent visual field loss and optic atroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…The IOP is lower in children than in adults. 20 There was no correlation with age in this series, probably owing to the limited age span.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The IOP is lower in children than in adults. 20 There was no correlation with age in this series, probably owing to the limited age span.…”
Section: Discussionmentioning
confidence: 58%
“…The variance was also of the same order. 20 The ICare was used in 152 school children. 5 This method was found to be highly reproducible and very comfortable.…”
Section: Discussionmentioning
confidence: 99%
“…1B). [44][45][46][47][48] Regression analysis of the compilation of multiple published studies [44][45][46][47][48] (Fig. 1B) gives the following logarithmic relationship between IOP and age, R 2 = 0.89: Intraocular Pressure ðmm HgÞ ¼ 9:95 þ 3:65logðageÞ: ð3Þ For each 567 mm of equatorial lens growth, IOP increases approximately 1 mm Hg [Eq.…”
Section: Intraocular Pressurementioning
confidence: 99%
“…Some investigators have reported on IOP measurement in children. [2][3][4][5][6] However, none of these studies reports on the performance of the recently introduced rebound tonometer (RBT) for the measurement of IOP in children, either those with normal IOP or those with ocular hypertension or glaucoma.…”
mentioning
confidence: 99%